Different Approaches to Modulation of Microglia Phenotypes After Spinal Cord Injury - Akhmetzyanova, Elvira; Kletenkov, Konstantin; Mukhamedshina, Yana; Rizvanov, Albert (Frontiers in Systems Neuroscience, 2019)
Microglial cells, which are highly plastic, immediately respond to any change in the microenvironment by becoming activated and shifting the phenotype toward neurotoxicity or neuroprotection. The polarization of microglia/macrophages after spinal cord injury (SCI) seems to be a dynamic process and can change depending on the microenvironment, stage, course, and severity of the posttraumatic process. Effective methods to modulate microglia toward a neuroprotective phenotype in order to stimulate neuroregeneration are actively sought for. In this context, available approaches that can selectively impact the polarization of microglia/macrophages regulate synthesis of trophic factors and cytokines/chemokines in them, and their phagocytic function and effects on the course and outcome of SCI are discussed in this review.